Advancing the sociopolitical view of supply chain management - Golgeci, Ismail; Roscoe, Samuel; Gligor, David Marius; Oh, Chang Hoon (Emerald, 2025)
Purpose World trade and global supply chains are undergoing seismic shifts due to rapidly shifting social trends, changing cultural norms and heightened geopolitical tensions among nation-states, including tariffs, trade wars and armed conflicts. This paper explores how political, social and cultural forces affect supply chains (SCs) and how SCs respond to these influences. It aims to define and promote a sociopolitical view of supply chain management (SCM). We achieve this by synthesizing insights from existing literature and examining emerging trends to develop a comprehensive framework that incorporates macro-, meso- and micro-level forces. The paper concludes by outlining a future research agenda to further the sociopolitical view of SCM. Design/methodology/approach We conduct a comprehensive text-mining exercise to explore the impact of sociopolitical forces, including government trade policies, tariffs and legislation, on the placement of SC infrastructure and trade flows. Our data sources comprise news databases, company websites and media outlets. Our analysis has identified multinational enterprises that relocated facilities or changed suppliers from China to other countries between 2018 and 2024, a timeframe characterized by significant sociopolitical upheaval due to the US–China trade war and the COVID-19 pandemic. Findings Our findings reveal a significant shift in production facilities and sub-tier suppliers away from China to countries such as Bangladesh, India, Vietnam and Mexico. Our analysis highlights not only the political factors, such as tariffs and trade wars, but also the social unrest that has driven these changes in SC designs. The findings inform a framework for advancing the sociopolitical view of SCM. Practical implications Policymakers can use the provided framing to support businesses and their global supply chains (GSCs) during periods of extreme social and political upheaval. Policy levers can include facilitating trade relationships with friendly nations, reducing trade barriers and supporting businesses with SC mapping analysis and visibility tools. Business managers are provided with a holistic understanding of the interactions between sociopolitical factors and GSCs to better prepare for future disruption events. Originality/value The mainstream SCM literature has viewed the impact of social trends, cultural norms and geopolitical tensions on SC flows in a piecemeal fashion. In an era characterized by geopolitical tensions, cultural shifts and regulatory changes, we argue that scholars must adopt a comprehensive, multilevel perspective to better analyze the sociopolitical forces at play in GSCs. This paper defines and advances a sociopolitical view of SCM to create a foundation for further research.
Keywords: Geopolitical disruptions; Sociopolitical view; Tariffs; Trade wars; Supply chain management; geopolitics